The first review on prenatal drug exposure and ocular malformation occurrence - Dubucs, Charlotte; Plaisancié, Julie; Courtade-Saidi, Monique; Damase-Michel, Christine (Frontiers in Pediatrics, 2024)
Even though a non-negligible portion of congenital eye anomalies has a clear genetic origin, an etiology is not found for most patients. Prenatal medication exposure is recognized to be involved in fetal malformations and several medications are specifically known to alter eye morphogenesis during embryonic development leading to congenital eye defects. We explored and reviewed the role of medications described in the genesis of ocular malformations, a role that has been little evaluated and probably still underestimated especially since several studies have shown the wide exposure of pregnant women to medication. We present our results in two sections; the first describes medications reported to be associated with ocular malformations in humans; the second details medications responsible for ocular malformations in animal models. We have summarized these results in tables, providing a relevant tool for clinicians. As most of the associations between medication exposure and congenital eye defects are either old or single case reports, this study highlights the needs for high epidemiological vigilance, accurate clinical description as well as a combination of studies on human genetics and experimental studies. Since medication exposures are potentially modifiable risk factors for congenital anomalies, this represents an important opportunity to implement preventive measures.